Erosion experiments of shale using a cavitation jet. (1st October 2022) - Chi, Peng; Shilong, Zhang; Jianhong, Fu; Qinfeng, Li; Yu, Su; Hao, Chang; Yuxuan, Chen; Yun, Yang
Abstract: Cavitation jet has been successfully utilized in onshore and offshore petroleum engineering. In this work, the feasibility of using a cavitation jet to drill and stimulate a shale gas reservoir is investigated. Erosion experiments of shale are conducted under various hydraulic conditions. It is found that the optimal standoff distance linearly increases with upstream pressure. As the upstream pressure increases from 40 MPa to 80 MPa, the maximum erosion rate rises from 0.80 mg/min to 2.22 mg/min. An incubation stage is not observed because of the poor ductility and malleability of shale. Under an upstream pressure of 60 MPa, the maximum cumulative erosion rate at unit jet power achieves the highest value of 1.40×10 −3  mg·min −1 ·W −1 . For shale drilling, a higher pump pressure is always in favor of a greater erosion rate, but the nozzle location needs to be adjusted to meet with the optimal standoff distance. For reservoir stimulation, an erosion time of 20 min is recommended. The promoted permeability is mainly attributed to the micro pores and fractures. Besides, the erosion mechanism is discussed concerning the periodic behavior and shedding frequency of cavitation cloud, as well as the development process of erosion pit on shale. Highlights: Erosion tests of shale are performed under various conditions using a cavitation jet. Optimal standoff distance linearly increases with pump pressure. Maximum cumulative erosion rate at unit jet power is 1.40×10 −3  mg min −1 ·W −1 . Promoted permeability is attributed to the pores and fractures of cavitation erosion. Erosion pits grow as the cementation is destroyed and mineral grains are peeled off.